Mid-term outcomes of lower limb salvage with 3D-printed ankle cages - Michael S. Kim, MD; Tara Mann, PhD; Cambre Kelly, PhD; Ryan C. Palmer, BS; Bijan Abar, MD, PhD; Hui Zhang, MD; Gerard J. Cush, MD (Foot & Ankle Surgery: Techniques, Reports & Cases, 2024)
Background: The challenge of surgical treatment of hindfoot collapse can be exacerbated by host conditions. Many patients with neuropathy, Charcot joint, or end-stage arthritis that undergo tibiotalocalcaneal (TTC) fusion with bulk allograft progress to nonunion and often require amputation. 3D-printed implants may improve outcomes within this population, but long-term outcomes of these implants have not yet been reported. This study reports mid-term outcomes of patients with Charcot arthropathy or end-stage arthritis who received 3D-printed titanium cage and dynamic hindfoot fusion nail combination fixation for limb salvage. Methods: This study was a retrospective review of consecutive patients who underwent hindfoot arthrodesis with a combination of patient-specific 3D-printed titanium cage and dynamic hindfoot fusion nail by a single surgeon at a single institution. The primary outcome was to establish the safety of the 3D-printed cage in a medically complicated population. The secondary outcome was to evaluate the efficacy of the 3D-printed cage, as evaluated by patient-reported pain score, ambulation status, and satisfaction. Deformity correction was evaluated by radiograph. Results: This study evaluated 13 cases with at least one year follow-up. Mean follow-up was 3.72 years (range 2.67-4.60 years). As of the most recent follow-up, 11 of 13 cages remain implanted, with two cages having been explanted in the setting of amputations indicated by conditions unrelated to the cage itself. Patients reported a mean pre-operative NRS pain of 6.6 ± 2.9 points. At the last follow-up, mean NRS pain was 2.0 ± 1.7 points. Pre-operatively, six of 13 patients reported the ability to ambulate independently without an assistive device. Post-operatively, 11 of 13 patients were able to ambulate independently. Conclusion: The results demonstrate no implant-related complications and promising outcomes in terms of fusion, deformity correction, and patient satisfaction, which are especially remarkable in the setting of Charcot arthropathy.